IDENTIFIKASI GUGUS FUNGSI SENYAWA PLAVANOID DARI EKSTRAK ETANOL DAUN AKAR BULU (Merremia Fitovilia) MENGGUNAKAN SPEKTROSKOPI FT IR - Ariandi; Nurasia; Sukarti; Ilmiati Illing (Universitas Cokroaminoto Palopo, 2019)
This study aims to identify the functional groups of chemical compounds from ethanol extract of akar bulu leaf (merremia fitovilia) using FT IR spectroscopy. M. fitovilia plant has been known by the people in Luwu as one of the traditional wound healing drugs in people with diabetes mellitus. The phytochemical test is known that the leaves of M. Fitovilia contains with flavanoid, alkaloids, steroids and phenolic compounds. In this study identification of functional groups of chemical compounds from the ethanol extracts of M.fitovilia leaves through sample preparation stages (sample collection, drying and sieving); extraction through ethanol maceration techniques, evaporation and FT IR analysis. The spectroscopic analysis of FT IR indicated that the ethanol extract of bilajang bulu leaves had functional groups of hydroxyl (OH), C-H aliphatic, carbonyl (C = O), olefin carbon (C = C), aromatic carbon, and alkoxy (C-O).